Alexandru Plămădeală – the sculptor of Bessarabian essences (Confluenţe Bibliologice, 2018)
In the article is described the exhibition dedicated to Alexandru Plămădeală, the great Bassarabian sculptor. The exhibition was organized on the occasion of the 130th anniversary of the birth of Alexandru Plămădeală in the reading room no. 3 Psychopedagogical, natural, real science. Arts of the Scientific Library USARB.
Keywords: Alexandru Plămădeală (1888 -1940); anniversary exhibition; collection of the USARB Scientiﬁc Library; Bessarabian sculptors